Young People Called "Unaccompanied Minors" and European Welfare States: A brief introduction to this special issue - Philipp Sandermann; Maren Zeller (Social Work & Society, 2017)
There are currently 65.6 million people who have become refugees worldwide. (UNHCR 2017) Many of these people try to make it to so-called Western welfare states. The latest peak of 2.0 million new asylum claims in 2016 confirms this trend: By the end of 2016, "with 722,400 such claims, Germany was the world's largest recipient of new individual applications, followed by the United States of America (262,000), Italy (123,000), and Turkey (78,600)." (UNHCR 2017) As a specifically categorized subgroup of young people who have been forcefully displaced as a result of persecution, conflict, violence, and human rights violations, and who fled without any legal guardian to assumedly safe(r) countries, so-called "Unaccompanied Minors (UAM)" symbolize this general development of flight and migration like few others. In 2015-2016, 300,000 young people became registered as UAM. (Unicef 2017, p. 6) This was neither a sudden development, nor was it unforeseen by those experts who had investigated the phenomenon for years and pointed at it to alert politicians and (social service) administrators across Europe and the world. Instead, the number of UAM increased rapidly and constantly during the last eight years, until the total number of asylum applicants considered to be UAM rose to approximately twenty times the original number in 2008.